Pandan City Library Dengan Pendekatan Arsitektur Kontemporer - Putri Rizki Ananda; Yohannes Firzal; Mira Dharma Susilawati (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pandan City which does not have a representative library and consisting of various ethnic groups and cultures, is very appropriate to give a touch that can be accepted by all people in the design. Designing a city library can also keep abreast of the current era. Therefore, the design with the Contemporary Architecture approach is considered appropriate for Pandan City Library. The research methods used include field data collection, literature studies and empirical studies. The results of this study are a City Library design with the application of the principles of Contemporary Architecture with case studies of library buildings in the last five years, namely the application of cantilever mass, atrium to impression of open space, gratings, transparent facades and greenroof.Keywords: City Library, Architecture, Contemporary